Detection of bacterial translocation during intestinal distension in rats using the polymerase chain reaction - Kazez, A; Saglam, M; Doymaz, MZ; Bulut, Y; Asçi, Z (Springer-Verlag, 2001)
To investigate whether distension Causes bacterial translocation (BT). a rat model reported earlier by us was used and to detect the presence of bacterial DNA in blood by polmerase chain reaction (PCR) assay the most sensitive detection method to date. In 4 groups of 4-week-old Wistar-albino rats a total of 15 animals each included. In the Ist group (distension + gavage). 10(10) Escherichia coli colonies were given via gavage and distension was carried Out by rectal air inoculation. In the 2nd group (gavage). animals ere inoculated With E. coli and no distension as induced. The 3rd group (distension) were only distended and no bacteria were inoculated. The control group were neither distended nor inoculated with E. coli. Blood samples were collected 3 h after manipulations and both blood Cultures and PCR assays were performed. According to the PCR results BT was evident in 80% of group 1.20% of group 2, and 33% of group 3 animals. BT was not determined in the control group. Significantly low percentages of positively were observed in blood cultures in all groups (P < 0.05). These results confirm reports that BT occurs in the presence of distension and that PCR is a superior way of determining BT. Thus. it Would be advisable to utilize PCR technology in cases where the possibility of distension exists. The early intervention might be useful before any severe clinical pathology (sepsis, multiple-organ-system failure) becomes evident.
17th Annual Meeting of the Turkish-Association-of-Pediatric-Surgeons (TAPS) -- SEP 26-29, 1999 -- ANTALYA, TURKEY
Keywords: bacterial translocation; intestinal distension; polymerase chain reaction